RPG Game “The English Kingdom” in English Learning - Subakti, Ketut Priadnyana Subakti; I Made Tegeh; I Gde Wawan Sudatha (Universitas Pendidikan Ganesha, 2024)
English language learning is an increasingly important need in the era of globalization, considering the role of this language as a means of international communication. However, students often consider conventional learning methods less enjoyable, especially at the secondary education level, thus reducing learning motivation and competency achievement. Gamification has been highlighted as an innovation that has increased student engagement in learning. This study attempts to integrate gamification into RPG game-based learning media that is feasible to use. This study aims to analyze the effectiveness of using The English Kingdom game in improving students' English skills, especially in vocabulary, grammar, and speaking. This type of research is development research. The subjects involved in this study were class VIII. The data collection method used was observation with quantitative data analysis. The RPG game product